Prarancangan Pabrik Etil Klorida Dengan Proses Hidroklorinasi Etanol Kapasitas 50.000 Ton Per Tahun - Karda, Irfani Dawamia, Ir. Nur Hidayati, M.T.,Ph.D, M. Mujiburohman, S.T., M.T., Ph.D (2017)
Preliminary design of ethyl chloride plant using process of ethanol hydrochlorination aims to meet the requirement of ethyl chloride in Indonesia. The plant with a capacity of 50,000 tons/year will be established in Solo, Central Java. Ethyl chloride is used for ethyl cellulose & ethyl alumunium production, and act as industrial solvent. Raction formation of ethyl chloride is divided to 2 steps, i,e: hydrochlorination ethanol and ethanol decomposition with a total conversion of 94.7%. Reaction is conducted in fixed bed multi tube reactor at a temperature of 325ᵒC and a pressure of 6 atm in gas phase condition. This process needs 4,523.71 kg/h ethanol and 3,566.80 kg/h hydrochloric acid to produce 6,313 kg/h ethyl chloride. The supporting utility unit provides 353,995.50 kg/h water which is supplied by Bengawan Solo river, 181,326.16 kg/h saturated steam which is produced of boiler with 10.21 m3/h fuel oil. The demand for electricity and fuel oil are 425 kW and 1,34 m3/h, respectively. Analysis economic conclude that percent Return On Investment (ROI) befor and after tax are respectively 34.13% and 17.07%. Pay Out Time (POT) before and after tax requires sequently 2.27 and 3.69 years. Break Even Point (BEP) is roughly 40.83% and Shut Down Point (SDP) is 25.46%. Disccounted Cash Flow (DCF) is approximately 30.38%. Therefore, this calculation exhibits that establishmnet of ethyl chloride plant is feasible. Keywords: ethanol, hydrochloric acid, ethyl chloride, fixed bed multi tube reactor